ANALISIS PERBEDAAN PENDAPATAN RATA-RATA PENGUSAHA DAN DAMPAKNYA UNTUK PERKEMBANGAN IKM (STUDI PADA TOKO MODERN) - Lailatus Saadah; Kismarotul Jannah (Sekolah Tinggi Pariwisata Mataram, 2021)
This study analyzes the difference in the average income of IKM entrepreneurs who enter modern shops, namely Indomaret and Alfamart. The purpose of this study is to determine the average income of IKM entrepreneurs who enter Indomaret and IKM entrepreneurs who enter Alfamart. In this study, there is the income of IKM entrepreneurs consisting of the average monthly income received by IKM entrepreneurs who enter Indomaret which is assessed in rupiah, and the average monthly income received by IKM entrepreneurs who enter Alfamart which is valued in rupiah. The number of samples in this study were 15 entrepreneurs, consisting of 10 IKM Indomaret entrepreneurs and 5 IKM Alfamart entrepreneurs. Data collection through interviews with IKM Indomaret and Alfamart entrepreneurs. To find out the difference in the average income of entrepreneurs between IKM Indomaret entrepreneurs and IKM Alfamart entrepreneurs using an independent T-test analysis.